The effect of Teach-back Method during discharge on the stress and anxiety of mothers of babies undergoing open heart surgery - Maryam Jangjoo; Firouzeh Moeini (Shahrekord University of Medical Sciences, 2023)
Background and aims: The research investigated the effect of care training during discharge on the stress and anxiety levels of mothers whose babies are undergoing open heart surgery. Parents of children with CHD experience high levels of stress and anxiety starting from the time of diagnosis, throughout the hospitalization for cardiac surgery, and even in the months and years that follow. Methods: In this quasi-experimental study, 60 mothers of children undergoing open heart surgery referred to the Tehran Children's Medical Center Hospital entered the study through lottery sampling in 2019. Then, the Teach-back Method program was implemented for the intervention group in four sessions. Data were collected before and immediately after the intervention using a Questionnaire measuring parents' stress and the Spielberger anxiety questionnaire. It was then analyzed using SPSS software version 16. Results: The study found that following the intervention, there was a significant decrease in the average scores of states and trait anxiety compared to the initial scores (P=0.006 and P=0.007, respectively). Additionally, the average stress score after the intervention was significantly lower than the initial score (P=0.001). Conclusion: The findings of this study suggest that offering oral instructions to mothers during the discharge phase of their children's open-heart surgery can lead to positive outcomes by reducing post-operative anxiety and stress. These results highlight the need for further research to explore the long-term effects of post-operative oral education in various clinical settings.